The model of the influence of service quality and marketing experience on customer satisfaction with brand equity as an intervening variable in bank jambi indonesia - Dahmiri Dahmiri (Management Department, Faculty of Economics and Business, Universitas Jambi, 2020)
The research objective was to analyze the of service quality effect and experiential marketing on customer satisfaction with brand equity as an intervening variable at Bank Jambi. This research is verification, which is to test the truth of a hypothesis. The unit of analysis in this study is Bank Jambi customers. Primary data is obtained by distributing questionnaires to 400 customers. Testing the hypothesis by analyzing Structural Equation Modeling (SEM). The results of the analysis conclude that service quality variables, experiential marketing and brand equity significantly influence Bank Jambi customer satisfaction both partially and simultaneously. Service quality and experiential marketing variables have a significant indirect effect on customer satisfaction through invervening brand equity variables. The model significant to explain all the variables but in the future needs more test for the other variables to make the model more precise. Service quality variables are more dominant variables affecting customer satisfaction. Increasing understanding about the model of the influence of service quality and marketing experience on customer satisfaction with brand equity as an intervening variable in indonesia jambi banks.